2023
DOI: 10.1038/s43587-023-00519-6
|View full text |Cite
|
Sign up to set email alerts
|

Senolytic therapy alleviates physiological human brain aging and COVID-19 neuropathology

Julio Aguado,
Alberto A. Amarilla,
Atefeh Taherian Fard
et al.

Abstract: Aging is a major risk factor for neurodegenerative diseases, and coronavirus disease 2019 (COVID-19) is linked to severe neurological manifestations. Senescent cells contribute to brain aging, but the impact of virus-induced senescence on neuropathologies is unknown. Here we show that senescent cells accumulate in aged human brain organoids and that senolytics reduce age-related inflammation and rejuvenate transcriptomic aging clocks. In postmortem brains of patients with severe COVID-19 we observed increased … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…For example, select biomarkers of cellular senescence in peripheral blood cells are associated with mild cognitive impairment in older adults [ 88 ], and cellular senescence has been shown to directly mediate cognitive function in old rats [ 89 ] and mice [ 90 ]. Moreover, senescent cells have been demonstrated to accumulate in aged human brain organoids [ 91 ] and in brains of mice with accelerated tau burden and the excess accumulation of senescent cells in both models can be suppressed with synthetic pharmacological senolytic therapy. Moreover, senolytic therapy reduces neurofibrillary tangles in mice with accelerated tau burden [ 92 ].…”
Section: Shared Molecular/cellular Mechanismsmentioning
confidence: 99%
“…For example, select biomarkers of cellular senescence in peripheral blood cells are associated with mild cognitive impairment in older adults [ 88 ], and cellular senescence has been shown to directly mediate cognitive function in old rats [ 89 ] and mice [ 90 ]. Moreover, senescent cells have been demonstrated to accumulate in aged human brain organoids [ 91 ] and in brains of mice with accelerated tau burden and the excess accumulation of senescent cells in both models can be suppressed with synthetic pharmacological senolytic therapy. Moreover, senolytic therapy reduces neurofibrillary tangles in mice with accelerated tau burden [ 92 ].…”
Section: Shared Molecular/cellular Mechanismsmentioning
confidence: 99%
“…The study demonstrates that the SARS-CoV-2 spike (S) protein causes the formation of multicellular syncytia, which are clusters of interconnected neurons and found that such fusion events severely compromised neuronal activity, as demonstrated by disruptions in calcium signaling within the neurons, suggesting that the neurological symptoms associated with COVID-19 [ 178 ]. Aguado et al use the human brain organoids to induce cellular senescence and mimic the SARS-CoV-2 infection process [ 179 ]. Senolytic therapy, which targets and eliminates senescent cells, has been shown to reduce inflammation and rejuvenate aging markers in the brain [ 180 ].…”
Section: Application Of Infection Model For Neurodegenerative Disease...mentioning
confidence: 99%
“…Senolytic therapy, which targets and eliminates senescent cells, has been shown to reduce inflammation and rejuvenate aging markers in the brain [ 180 ]. Additionally, this therapeutic approach can block viral replication and prevent cellular senescence in brain organoids infected with SARS-CoV-2 [ 179 ]. Wang et al develop a pericyte-containing cortical organoids model to mimic the NVU and study SARS-CoV-2 neuropathology [ 181 ].…”
Section: Application Of Infection Model For Neurodegenerative Disease...mentioning
confidence: 99%
“…Often associated with increasing age, these cells have been implicated in multiple age-related neurodegenerative diseases 13,14 . The selective clearance of SCs results in alleviation of disease symptoms and progression [15][16][17] , extension of lifespan 18,19 , and improved healthspan 20,21 . Interestingly, MS has been shown to be a disease of accelerated aging 22 , and recent evidence of SCs in MS lesions has been reported [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%